Revealing lexical bundles of non-native English essay at a private Islamic university: A corpus-based evaluation - Fauzul Etfita; Sri Wahyuni; Arimuliani Ahmad; Wasana Saranga Sudusinghe; Chandima Kumara Walpita Gamage (English Learning Innovation, 2025)
Lexical bundles are a crucial element for Foreign Language Learners (FLL) as they facilitate the acquisition of new vocabulary and enhance fluency. Such multi-word statements confer a natural structure to language and enhance successful communication in both spoken and written forms. Although numerous studies address lexical bundles, research on their application in English writing or inside Indonesian EFL classes is notably scarce. The study employed a corpus methodology, utilizing AntConc software version 3.5.9 to categorize lexical bundles from student essays. The output comprised 17,100 varieties of N-gram lexical bundles, specifically three, four, five, and six-word bundles. The study revealed regular use of formulaic and repetitious bundles, including "at least one foreign language," "a foreign language," and "violent video games." Students' writing was dominated by these sentences, which suggested a reliance on memorized forms and a small range of scholarly discourse markers. Although three- and four-word bundles were most popular, longer five- and six-word bundles, though less common, showered better meanings and more formulaicity. These results imply that although students have come across lexical bundles, their usage is limited to known themes and lacks a more general academic background. To improve EFL students' academic writing abilities, the study underlines the requirement of explicit instruction on lexical bundles, especially those fulfilling argumentative and coherent purposes. The findings provide pedagogical ideas for including corpus-based tactics into writing education to support fluency, coherence, and lexical variation